OPERATION OF ORCHID PORT IN NORTH GORONTALO REGENCY IN (2002-2020) - Lamasay, Sintia; Mohamad, Sutrisno; Manay, Helman (CV. Fahr Publishing, 2024)
This research aims to reveal the process of developing the Anggrek port in North Gorontalo Regency, and how the port influences economic development in North Gorontalo Regency. The research uses historical research methods with the discipline of History covering four stages of data collection, namely heuristics of source collection, source criticism, interpretation or interpretation of sources and historiography. The results of the research show that the Anggrek port has existed and started operating since 1997. Then in 2001 the port was planned by the Directorate General of Sea Transportation (Ditjen Hubla) and the Indonesian Republic Department of Transportation to become the main port. The presence of the Anggrek port in northern Gorontalo will certainly have a big impact on the regional economy as well as the economy of the local community.